2009
DOI: 10.1164/rccm.200806-953oc
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Disease–associated Pulmonary Arterial Hypertension in the Modern Treatment Era

Abstract: Survival of patients with SSc-PAH in the modern treatment era is better than in historical series. A significant proportion of patients with mild functional impairment or exercise-induced SSc-PAH have evidence of disease progression. Survival of patients with respiratory disease-associated pulmonary hypertension is inferior. SLE-PAH has a better prognosis than SSc-PAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
542
9
18

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 595 publications
(605 citation statements)
references
References 16 publications
36
542
9
18
Order By: Relevance
“…Isolated survival of SSc patients with PAH while receiving pulmonary vasodilator therapy was recently reported to be 78% (1-year rate), 68% (2-year rate), and 47% (3-year rate) (7,19,20). Importantly, Tolle and coworkers have suggested that exercise-induced pulmonary hypertension (PH) may represent an intermediate phenotype "between" normal and resting PH (21).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolated survival of SSc patients with PAH while receiving pulmonary vasodilator therapy was recently reported to be 78% (1-year rate), 68% (2-year rate), and 47% (3-year rate) (7,19,20). Importantly, Tolle and coworkers have suggested that exercise-induced pulmonary hypertension (PH) may represent an intermediate phenotype "between" normal and resting PH (21).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, Tolle and coworkers have suggested that exercise-induced pulmonary hypertension (PH) may represent an intermediate phenotype "between" normal and resting PH (21). In addition, Condliffe and coworkers found that 19% of SSc patients with PAH who had exercise-induced PH developed resting PAH after ϳ2.3 years (19). Others, however, have argued that a certain degree of exerciseinduced PH may be explained by increasing age, persistent hypoxia, and/or systemic hypertension (22,23).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Это мнение подтвержда-ется и другими авторами, обнаружившими, что у 19% па-циентов с ССД, продемонстрировавшими СИ-ЛГ, разви-вается ЛГ в покое в течение примерно 2,3 года [21]. Таким образом, выявление СИ-ЛГ у пациентов с ССД может по-мочь ранней установке диагноза, инициации терапии и, возможно, улучшению прогноза [22].…”
Section: таблица 2 сравнительная характеристика больных ссд в зависиunclassified